Pullback Attractors for Nonautonomous 2D-Navier-Stokes Models with Variable Delays - Xiaoli Liu; Yejuan Wang (Abstract and Applied Analysis)
Using a method based on the concept of the Kuratowski measure of the noncompactness of a bounded set as well as some new estimates of the equicontinuity of the solutions, we prove the existence of a unique pullback attractor in higher regularity space for the multivalued process associated with the nonautonomous 2D-Navier-Stokes model with delays and without the uniqueness of solutions.